Noncontact UHV-AFM investigations of the growth of C59N films on layered materials - Sommerhalter, Ch.; Pietzak, Björn; Lux-Steiner, M. Ch.; Nuber, Berthold; Reuther, Uwe; Hirsch, Andreas (Surface Science, 1999)
Submonolayer films of the heterofullerene CN were grown by evaporation in ultra-high vacuum onto the layered materials graphite (HOPG), WSe and mica at different substrate temperatures. The growth of the CN films was investigated by atomic force microscopy (noncontact UHV-AFM) and compared with that of C. We found distinct differences in the shape of the islands formed by the two materials. Whereas C nucleates in well-shaped trigonal and hexagonal islands, CN forms extended dendritic agglomerates under similar conditions. Only at higher temperatures (above 523 K) are compact and oriented islands also formed for CN. The formation of dendroids indicates that CN sticks strongly to the edges of the islands. The mobility of CN on HOPG and WSe is rather high and comparable to that of C on these materials. On mica, only small islands are observed for both C and CN, indicating a low mobility of both materials.